How The Cyberspace Affect the Cooperation Among the States in the Field of Human Rights - HASSAN, Mahdi Musse (Cyberpolitik Journal, 2023)
The developing influence of cyber activities in social, economic, political, and military spheres provided cyberspace with an indispensable feature of human life and security. With the rapid growth of cyberspace in this modern society since the introduction of the internet and gigantic digital devices with their indisputable good side, there are also critical challenges and threats led by the internet and digital devices. The bad and good sides of cybersecurity affect the different levels of society, whether normal individuals, business organizations, international organizations, or even governments. Creating mechanisms and answering the consequence of cyber attacks to control the cyber threats appeared to harm the fundamental human right. Since that period, many states have taken the issue seriously regarding ordinary individuals and organizations who meet daily critical cyber-attacks and threats. For instance, 2007 was a cornerstone period of the emergence of global concern about cyber threats when the entire nation of Estonia experienced a large-scale cyber attack. This incident has turned international attention and worries into cyber threats. Currently, nation-states have engaged the sett up regulations and approaches to prevent or minimize the dangers that can be caused by cybersecurity. The developed technological and economic states have shown high doubt between them caused by cybersecurity attacks. Thus, this article explores cyberspace touch the cooperation between the nations in the field of human rights. The paper also focuses on how basic human rights should be respected and protected while implementing the mechanism against cybersecurity. Although nation-states are essential actors in cyber and cybersecurity, it is inevitable to cooperate to achieve a suitable solution for cyberattacks. The paper concludes some state cooperation appeared in the last years, while others attempt to develop cybersecurity which can harm the security of other nations. It is unavoidable to collaborate between the state to reach appropriate and effective responses, which is desired during any cyber attack. In the end, the article also underlined obtaining cooperation among states to establish an uninterrupted multilateral network to defend the cyber threats via guaranteed shared cybersecurity.